Deep Learning Supported by Desmos Classroom to Improve Problem-Solving Skills and Regulate Students’ Emotions - Tita Novia; Beni Junedi; Sarah Caesarani (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
Mathematical problem-solving skills are one of the key competencies students must possess in mathematics education. However, in reality, many students still struggle to solve mathematical problems, particularly those involving linear equations. In addition to cognitive factors, affective aspects—such as emotional regulation—also influence students’ success in the learning process. Therefore, there is a need for instructional innovations capable of enhancing mathematical problem-solving skills while simultaneously supporting students’ emotional regulation. This study aims to determine the effect of Desmos Classroom-assisted deep learning on students’ mathematical problem-solving skills and emotional regulation regarding linear equations. This study employed a quasi-experimental method using a Nonequivalent Control Group Design. The study population consisted of eighth-grade students at SMP Negeri 3 Kalanganyar. The sample comprised an experimental class that received deep learning instruction supported by Desmos Classroom and a control class that received conventional instruction. The instruments used included a mathematical problem-solving ability test and a student emotional regulation questionnaire. Data analysis was conducted using descriptive and inferential statistics through hypothesis testing. The results indicate that deep learning instruction supported by Desmos Classroom has a positive effect on students’ mathematical problem-solving skills. This is evidenced by an increase in the students’ average score from 57.15 on the pretest to 71.63 on the posttest. The results of the hypothesis test also showed a significance value of 0.000, which is less than 0.05, indicating a statistically significant difference following the implementation of the instruction. In addition, students’ emotional regulation achieved an average percentage of 76.08%, which falls into the “very good” category. Thus, deep learning instruction supported by Desmos Classroom can serve as an effective alternative for improving students’ mathematical problem-solving skills while simultaneously supporting their emotional regulation when studying linear equations